Optimality and Duality for Second-order Multiobjective Variational Problems (European Journal of Pure and Applied Mathematics, 2010)
In this work, we first modify a converse duality theorem for second-order dual of a scalar variational problem. We then consider its multiobjective analogue and obtain necessary optimality conditions and duality relations. At the end, the static case of our problems has also been discussed.